Smallholder African agriculture: progress and problems in confronting hunger and poverty - Resnick, Danielle (International Food Policy Research Institute, 2004)
In contrast to uniformly pessimistic assessments about Sub-Saharan Africa’s (hereafter Africa) ability to meet the Millennium Development Goals (MDGs), this paper examines recent trends in poverty, malnutrition, and growth to delineate where the challenges are the greatest within the entire region and sub-region and to highlight informative cases of success in specific countries. The performance of agriculture, especially smallholder agriculture, receives particular attention due to its role in sustaining the livelihoods of a majority of Africa’s poor. In recent years, the importance of smallholder agriculture has been greatly recognized, demonstrated by both African governments and the donor community pledging to engage in the requisite interventions for generating agricultural growth. By seizing on this new enthusiasm and learning from case studies of smallholder successes, agriculture could significantly contribute to Africa’s ability to meet the MDGs.